Political Leadership vs. Prime Ministerial Leadership: Evolution of the Priorities in Decision-Making Reform in Japan (New Dynamics in Asia, 2020)
The slogans of “political leadership” (seiji shudō) and “prime ministerial leadership” (Kantei shudō) have been commonly used to describe the institutional reforms in Japan in the last three decades. The former term referred to the supremacy of the politicians over the bureaucrats, and the latter to the strengthening of the powers of the head of government. The aim of this chapter is to clarify differences and similarities between the two concepts, as well as to compare their applicability to decision-making patterns under subsequent governments. It is argued that different prime ministers put emphasis on either the former or the latter concept.